Comparison of agar dilution, microdilution, and disk elution methods for measuring the synergy of cefotaxime and its metabolite against anaerobes. - Smith, J A (1986)
The activities of cefotaxime (CTX) and desacetyl cefotaxime (des-CTX) were tested both singly and in combination against 173 anaerobic clinical isolates. The MIC of CTX for 50% of 60 Bacteroides fragilis isolates was 22.4 micrograms/ml in broth, compared with 47.4 micrograms/ml in agar. This reduced efficacy in agar was seen with all species tested and is in apparent conflict with reported clinical efficacy of the drug. Synergy between CTX and des-CTX was observed with 70 to 100% of the isolates, including 60% of all Bacteroides spp. tested. The susceptibility results in a synergy system correlated well with those noted in a broth-disk elution method incorporating 32 micrograms of CTX and 8 micrograms of des-CTX per ml. The correlation was poorer when the broth-disk method contained 16 micrograms of CTX and 8 micrograms of des-CTX per ml.